PERILAKU SOSIAL ANAK PEKERJA BATU KALI DI KAMPUNG TAPAK LEBAR - Mansyur Romadon Putra (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
The purpose of this study is to describe the social behavior of the children of river stone labour in Tapak Lebar village in a primitive social condition along the river bank. As the research subjects, the research involved three children of 5-6 years old. The research was conducted for 8 (eight) months starting from January through August 2015. The research belonged to qualitative research and was classified as an ethnography research. The data was collected by observation, document study, field notes to be analyzed employing Spradley model. The research findings indicate the social behavior of the children in Tapak Lebar village in interacting each other do not reflect etiquette and politeness suitable to polite culture. It is recommended that the local government implement socialization program to anticipate and to prevent the social behavior of the river bank children by establishing educational institutions for them.